Blue Economy from Perspective of Al-Qur’an - Sultoni, Ahmad Hery; Anwar, Hamdani; Febriani, Nur Arfiyah (Jurnal Indonesia Sosial Sains, 2024)
This research concludes that from the Al-Qur'an perspective, the maritime concept with a blue economy perspective is an integral approach, where the utilization of marine resources, which are referred to as al-Bahr and al-yam in the Al-Qur'an, needs to integrate several aspects interrelated maritime affairs. Reduction of one maritime aspect can result in ineffectiveness in dealing with the complexity of maritime problems as a whole. The framework used in this research includes the following aspects: First, Aqidah: Humans are seen as caliphs who are responsible for the universe that Allah rules. Second, Sharia: Maritime natural resource utilization activities must be in accordance with the principles of Islamic law. Third, Morals: Improvement with adaptive innovation for the efficiency of natural resources, fair distribution, and consumption that does not damage or waste natural resources. This research supports the views of several figures such as Robert Maltus, Langdon Gilkey, Seyyed Hossein Nasr, Donella H. Meadow, Arne Naess, Edith Brown Weiss, and Gunter Pauli, who emphasize the need for wise management of natural resources for sustainability. The research method used is a qualitative method with the Tafsir Maudū'i (thematic) interpretation method. This research differs from the views of several figures, such as Hugo Grotius, Adam Smith, David Ricardo, Immanuel Kant, and Garret Hardin, who have different views regarding natural resource management. Thus, this research proposes a holistic approach based on Islamic values in viewing and managing marine resources to achieve economic and environmental sustainability.